Clarifying the problem of food loss and waste to improve food and nutrition security - Torero, Máximo; Delgado, Luciana; Schuster, Monica; Sethi, Geetha; Nakasone, Eduardo; Piñeiro, Valeria (T20 Argentina, 2018)
Reducing food loss and waste can contribute to food security and sustainability. Measuring food loss and waste (FLW), identifying where in the food system it occurs, and developing effective policies along the value chain are essential first steps toward addressing the problem. The G20 can play a crucial role with three main actions: (1) Mainstream the implementation of a Global Baseline of FLW with a common and validated measurement methodology across the value chain with concreate targets at regional and country level; (2) Promoting the implementation of context-specific costbenefit analyses must be systematically carried out to identify the most sustainable, cost, energy, and socially-efficient FLW reduction interventions; and (3) Promoting the coordinating between MDBs, Regional Banks and International Organizations through the technical platform on measurement and reduction of food loss and waste launched by IFPRI and FAO as result of the Turkey G20 on December of 2015.